Myth Creation in the Poetic Evolution of P. A. Oyunsky - Romanova, Lidia Nikolaevna (Journal of History Culture and Art Research, 2018)
The article discusses the features of myth creation in the poet art of the founder of Yakut Soviet literature, Platon Alekseyevich Oiyunsky. Based on the theoretical and methodological developments of profound researchers of mythology, such as E.M. Meletinsky, U.M. Lotman, V.N. Toporov and others as well as the modern-day researchers of the Formation Period of Soviet literature, such as A. Gennep, J.C. Günther, E. Dobrenko, K. Clark and others, we have overviewed the main aspects of the main mythological plots, motifs, and images functioning in the civil and philosophical lyrical poetry of the Yakut poet. We also justify the fact that while Oiyunsky turned to mythology in different periods of his creative life, his mythology-creating technique evolved together with his personal ideological principles and with the ideological trends of that time. In the early period of his creative life, the transforming mythological ideology holds strong positions in his civil lyrical poetry; this kind of poetry implies moving from chaos to creation. In this aspect, the perception of myths in the creative works by Oiyunsky is studied consecutively in accordance with the rituals of transitioning (according to the classification given by Gennep): from the renunciation (destruction) of the old world to a preliminary stage of creation, and finally – the creation of the new world. It has been clearly defined that the permanent motifs of chaos cosmic nature and the transition from darkness to light, sacrifices made in the name of the good as well as deaths and resurrections hold a special place in the mythological model of world creation (the victory of the Soviet power and the triumph of the socialism ideas). The creation of a new type of main character, similar in terms of structure to the mythological character represented in the culture, also speaks in favor of Oiyunsky’s creative tendency towards mythology in his poetry. The author of the present article makes the following hypothesis: apart from using myths in the organization of heroic, patriotic and pathetic text structures, Oiyunsky creates an exceptionally novel type of mythological perception, which establishes a new level of creative thinking encompassing the most fundamental features of human existence. Mythology in creative works of Oiyunsky plays an important role in creating the lyrical motifs in his poetry. Myths attain a new language form in his poetry, thus, expressing his world perception.